2011
DOI: 10.5424/fs/20112003-11084
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for evaluating process-based models of gas exchange

Abstract: Physiologically-based (or process-based) models are commonly applied to describe plant responses mechanistically in dependence on environmental conditions. They are increasingly evaluated with eddy-covariance measurements that integrate carbon and water exchange of an area of several hectares (called the fetch). However, almost all models applied to date in such exercises have considered only the dominant tree species and neglected other species that contributed to the measured gas exchange rates-either in sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…LandscapeDNDC links modules describing microclimate, water cycle, soil-biogeochemistry, plant physiological processes and dimensional changes by daily time step integration. All processes and state variables are considered in a vertically structured one-dimensional column including tree canopy, humus horizons and mineral soil [36]. Detailed process descriptions and evaluations have been reported in earlier studies including water balance [37,38], soil respiration and N trace gas emission [39] and nitrate leaching [40].…”
Section: Model Frameworkmentioning
confidence: 99%
“…LandscapeDNDC links modules describing microclimate, water cycle, soil-biogeochemistry, plant physiological processes and dimensional changes by daily time step integration. All processes and state variables are considered in a vertically structured one-dimensional column including tree canopy, humus horizons and mineral soil [36]. Detailed process descriptions and evaluations have been reported in earlier studies including water balance [37,38], soil respiration and N trace gas emission [39] and nitrate leaching [40].…”
Section: Model Frameworkmentioning
confidence: 99%
“…However, without analysing the net ecosystem exchange (NEE) of CO 2 , it is difficult to judge the system's response as a net warmer or cooler of the atmosphere. However, the modelled NEE values for birch forests in Finland show that these ecosystems are net sinks of atmospheric carbon (Grote et al 2011), which was also confirmed in the Estonian case study . The average methane flux for the whole study period was almost below zero, meaning that the stand is consuming CH 4 (Fig.…”
Section: Nitrogen Fluxesmentioning
confidence: 52%
“…carbon exchange and biomass allocation, have been determined from literature sources and were evaluated using beech trials at other investigation sites (Grote et al 2011a). The setup of a cohort simulation and an application for a mixed stand dominated by Scots pine have been presented in Grote et al (2011b).…”
Section: Model Descriptionmentioning
confidence: 99%
“…It provides a high spatial differentiation of processes and runs in subdaily to daily time steps, and it is very sensitive to uncertainties in individual initialization (Fontes et al 2010), costly in parameterization and comparatively slow. To reduce complexity while preserving a high degree of mechanistic description, Grote et al (2011b) have represented stand structure in MoBiLE-PSIM as an ensemble of spatially interacting single species cohorts, where each cohort consists of trees that are identical in dimension and are ordered on a regular grid. Presuming this approximation, competition may be covered by exclusively simulating one representative tree per cohort, and computational efficiency is increased by an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%